Neuronal cells from bipolar individuals are more susceptible to glutamate induced apoptosis than cells from non-bipolar subjects - Hu, Ming; Gao, Yonglin; El-Mallakh, Rif S (Journal of affective disorders, 2021)
•Olfactory neuroepithelial progenitor (ONP) cells are a novel cellular model that allows for the examination of neuronal cellular physiology with the preservation of disease-specific physiology.•ONPs derived from individuals with bipolar type I illness are more susceptible to glutamate induced apoptosis that cells derived from individuals without bipolar disorder.•Lithium antagonizes glutamate induced apoptosis more effectively in ONPs derived from subjects with bipolar disorder than in non-bipolar controls.•The anti-apoptotic effect of lithium is associated with increases of B-Raf and Bcl-2 protein expression. Bipolar disorder (BD) is associated with marked parenchymal brain loss in a significant fraction of patients. The lack of necrosis in postmortem examination suggests an apoptotic process. Emerging evidence suggests that mood stabilizers, like lithium, have antiapoptotic actions. Glutamatergic abnormalities have been associated with BD. Olfactory neuroepithelial progenitors (ONPs) harvested by biopsy from type I bipolar patients (BD-ONPs, n = 3) and non-bipolar controls (non-BD-ONPs, n = 6), were treated with glutamate at concentrations sufficient to mimic the observed doubling of intracellular sodium known to occur in both mania and bipolar depression, to investigate potential differential lithium effect on both BD-ONPs and non-BD-ONPs. Apoptosis was detected in BP-ONPs exposed to 0.1 M glutamate for 6 h but in non-BD-ONPs at 24 h. Moreover, after treatment with 0.1 M glutamate treated for 6 h the levels of the pro-apoptotic cleaved-caspase-3 and cleaved-PARP proteins were significantly higher in BD-ONPs compare to non-BD-ONPs. Pretreatment with a therapeutic concentration of 1 mM lithium for 3 days attenuated the glutamate induced apoptosis. Lithium pretreatment 3 days also prevented the DNA fragmentation induced by glutamate, and significantly increased the antiapoptotic phospho-B-Raf and Bcl-2 proteins in BD-ONPs compared to non-BD-ONPs. ONPs are obtained from subjects with and without bipolar illness, but outcome of their study may still not reflect the biology of the illness. ONPs derived from BD are more susceptible to glutamate-induced apoptosis. Lithium is associated with a greater increase of anti-apoptotic B-Raf and Bcl-2 expression in BD-ONPs.